Landasan Filosofis Pembelajaran Bahasa Inggris Di Indonesia - Haerazi Haerazi (Mandala, 2018)
The Indonesian curriculum for junior and senior high school level always undergoes a revision. This is aimed at finding the good patterns practically and theoretically to reach the goals of national education that are to educate whole Indonesian societies. Through curriculum changes, the teachers hope they can develop their students’ competences holistically in social attitude, skills, and knowledge. Theoretically, the educational curriculum from 1994 to 2013 always refers to educational philosophies. This paper shows the curriculum analysis based on educational philosophies. Dealing with the result of curriculum analysis, the educational philosophies in Indonesian curriculum are progressivism, constructivism, and humanist-religious. These educational philosophies are deemed dominantly affecting the Indonesian curriculum nowadays. For English language learning, those philosophies are adopted. It can be seen from language philosophy referred, and language learning theory applied. This analysis is based on the appropriateness of language approach, method and technique applied in classroom as a mirror of educational philosophy that follows.